Nanosecond Responses of Proteins to Ultra-High Temperature Pulses - Steel, Bradley C. (Biophysical Society, 2006)
Observations of fast unfolding events in proteins are typically restricted to <100°C. We use a novel apparatus to heat and cool enzymes within tens of nanoseconds to temperatures well in excess of the boiling point. The nanosecond temperature spikes are too fast to allow water to boil but can affect protein function. Spikes of 174°C for catalase and ∼290°C for horseradish peroxidase are required to produce irreversible loss of enzyme activity. Similar temperature spikes have no effect when restricted to 100°C or below. These results indicate that the “speed limit” for the thermal unfolding of large proteins is shorter than 10(−8) s. The unfolding rate at high temperature is consistent with extrapolation of low temperature rates over 12 orders of magnitude using the Arrhenius relation.